(untitled) (Third Sector Social Economic Review, 2020)
The effective and rapid change in the use of social media tools has caused hotel businesses to shift their marketing strategies in this direction. Hotel businesses use social media tools for purposes such as product and service promotion, reaching more consumers, interacting with customers, creating brand loyalty. The purpose of this study is to determine how 5-star thermal hotel businesses in Afyonkarahisar use Facebook and Instagram as a marketing tool, and what information they provide on Facebook and Instagram pages. The scope of the research includes 11, 5-star hotel businesses operating in Afyonkarahisar. The shares of hotel businesses on Facebook and Instagram pages were analyzed by content analysis method. As a result of the research, it has been revealed that the number of hotels, where the hotel businesses provide basic information on Facebook and Instagram pages, share photos and videos, but do not organize campaigns that will keep the pages alive, and offer online booking services that will force consumers to purchase.